Implementasi Model Pembelajaran Sains, Technology, Engineering, and Mathematics (STEM) pada Mata Pelajaran IPS dalam Meningkatkan Hasil Belajar Peserta Didik di SMP Negeri 3 Jakarta - Ellena Evelyn; Desy Safitri; Saipiatudin Saipiatudin (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This study aims to improve students' learning outcomes in Social Sciences (IPS) through the implementation of the Science, Technology, Engineering, and Mathematics (STEM) learning model. The background of this study is based on the low learning outcomes of IPS in class VII of SMP Negeri 3 Jakarta, as well as the lack of variations in innovative learning models. The study used the Classroom Action Research (CAR) method of the Kemmis and McTaggart model which was carried out in two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. The subjects of the study were 36 class VII-B students. Data collection techniques used learning outcome tests, observations, interviews, and documentation. The results of the study showed a significant increase in student learning outcomes. In the first cycle, the percentage of students who achieved the Minimum Completion Criteria (KKM) was 77.77%, increasing to 91.6% in the second cycle. In addition, student activity in learning activities also increased. These results prove that the Science, Technology, Engineering, and Mathematics (STEM) learning model is able to integrate social studies concepts with real situations, thus facilitating students' understanding and improving the quality of learning.